"You Adore a God Who Makes You Gods": Augustine's Doctrine of Deification - Reardon, Michael M. C. ca. 20./21. Jh. (Horizons, 2024)
Twentieth-century theologians advanced a consensus position that the doctrine of deification was alien to Augustine's theology - even impossible to square with his other commitments - and that even if traces of the doctrine could be detected, they were, at best, of marginal importance to his intellectual topography. This position, however, has been persuasively challenged by several investigations during the past three decades. This article builds upon these latter investigations to demonstrate how the notion of deification is prevalent throughout his corpus - whether linguistically evident by his use of technical terms such as deificare and cognates, or more often, conceptually in his reflections upon anthropology, Christology, and ecclesiology. The article concludes by noting two of Augustine's distinctive contributions to the post-Nicene development of deification - that is, an emphasis upon the sacramental and ecclesiological contours of the doctrine.